Unmethodical publication of scientific papers - Valenzuela, Germán (2008)
Publication of a medical paper allows investigators to communicate their ideas and give the results of their research, conditioning they can be probed and replicated by fellow counterparts. Sometimes, the number of publications is used as a measure of scientific ranking and the quality of publications is determined by the journal in which they appear. However, we find irregularities in the publication of scientific papers, including authorship, data management, duplication or ghost publication, and conflict of interests.